Stress Management (Repetitive Prayer: Al-Fatihah) on Stress Levels in Pregnant Women - Rose Nanju; Ratna Hidayati; Laviana Nita Ludyanti; Peny Tyas (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2022)
Stress in third-trimester pregnant women is often experienced due to physical and psychological changes. A spiritual intervention that can be applied is the Repetitive Prayer: Al-Fatihah therapy for stress levels in pregnant women. The purpose of this study was to determine the effect of stress management (Repetitive Prayer Al-Fatihah) on stress levels in pregnant women at Pare health center, Kediri Regency. Pre Experimental research design (One Group Pre-Post Test Design). The sample size was 14 respondents using accidental sampling. Data were analyzed using the Wilcoxon Test. The results obtained before the intervention showed that most respondents (64.3%) had moderate stress levels. Meanwhile, after the intervention showed that most of the respondents (64.3%) experienced a decrease in stress levels in the mild stress category. The results of the Wilcoxon Test show the effect of stress management (repetitive prayer: Al-Fatihah) on the stress level of pregnant women at pare health center Kediri Regency with p-value = 0.002 <α = 0.05. This intervention contains asy-syafiyah (healer), asy-syukr (gratitude), and ar-ruqyah (incantation) which sound waves transmitted to the cerebral through the primary visual cortex transmitted to the left angular gyrus, Wernicke's area, Broca's area, and motor cortex thereby increasing production of endorphins which reduce stress in third-trimester pregnant women. It is recommended that third trimester pregnant women perform this non-pharmacological therapy to reduce stress regularly experienced during worship and leisure time.